Mutual Funds Performance: Conventional and Sharia Product - Agussalim, M.; Limakrisna, Nandan; Ali, Hapzi (International Journal of Economics and Financial Issues, 2017)
Mutual fund investment is one of the instruments that are being developed,with the advent of the Indonesian capital market. In progress, mutual the first apply the principle of sharia in running strategy business and be an option investors to invest. A fundamental difference between a mutual fund conventional with mutual funds sharia at investment policy .A mutual fund sharia use investment policy through selection process in the formation of portfolio and strategies management using the principle islamic. This study aims to see how performance between a mutual fund conventional and sharia. Sample used in this research is a stock mutual fund conventional and Islamic products. Data used in the form of secondary data Net Assets Value per Unit (NAV/unit), Composite Index (IHSG), Jakarta Islamic Index (JII) and a data rate of Sertifikat Bank Indonesia (SBI) and Sertifikat Bank Indonesia Syariah (SBIS) the period 2007-2014. The mutual fund performance seen of its rate of return and risk as well as the measurement method using the Sharpe index, Treynor index and Jensen's Alpha. The tools used statistical test is ver.21 with SPSS statistical methods test the hypothesis testing independent sample t-test. Research results with the alpha (Î±) 5% showed no difference in performance between conventional and sharia mutual funds seen from the level of risk and Sharpe index method. While the rate of return and the measurement method also Treynor Index Jensen 'Alpha, the research results with the alpha (Î±) of 5% in a given year shows there is a difference in performance between conventional and sharia mutual funds in the study period of 2007 - 2014. The results show the performance of mutual funds conventional better than sharia mutual funds seen from the level of return and the Sharpe Index. When viewed from the level of risk, Treynor index and Jensen's Alpha results show the performance of conventional mutual funds is lower than the sharia mutual fund. Keywords: Conventional Mutual Funds Performance, Sharia Mutual Fund Performance, Return, Risk, Sharpe index, Treynor index and Jensen's Alpha. JEL Classification: G11